Linear assignment procedures - Jonker, R; Volgenant, A (European journal of operational research, 1999)
The linear assignment problem (LAP) is both useful itself as well as a relaxation for difficult conbinatorial optimization problems like quadratic assignment and the Traveling Salesman Problem. Different types of algorithms are available for LAP. An overview of the available procedures is given.